Pembinaan Pembelajaran Kaligrafi Al-Qur'an Berbasis Pembelajaran Kooperatif - Setiawan, Ade; Vestia, Etika; Satrial, Ardi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
This paper aims to describe the pattern of fostering Al-Qur'an calligraphy learning. The research method uses descriptive qualitative. Data collection techniques were interviews, observation, and documentation. The informants of this study were trainers and students in fostering Al-Qur'an calligraphy learning at the Development Institute for Tilawatil Qur’an (LPTQ) West Sumatra. The results of this study found that the pattern of coaching learning of Al-Qur'an calligraphy includes aspects of strict quality management and quality starting from input, process, and output. Quality input indicators are the qualifications of students and trainers. In the learning process aspect, two essential indicators support the achievement of higher-quality output: the quarantine system and the application of cooperative learning strategies. In addition, cooperative learning-based Al-Qur'an calligraphy development pattern has six work steps, including determining tasks, determining partners, implementing, investigating the correction team, products, and awards.